The endpoint epidemic of IoT – just a bad dream?. Issue 4 (April 2019) - Giese, Sascha
Abstract : Over the past decade we've heard a lot of concern from security vendors about the rise of the Internet of Things (IoT) and the growth of smart devices. On a daily basis, technology professionals are struggling to keep their organisations secure, even though the endpoint epidemic that has kept experts up at night hasn't fully manifested itself in the way we feared. The growth of the Internet of Things (IoT) has been a key theme of the past few years but the endpoint epidemic that has kept experts up at night hasn't fully manifested itself in the way we feared. Yet despite its slow burn, IoT should remain a top priority for today's cyber security professionals. A self-healing, automated network can detect threats, keep data from being compromised and reduce downtime. Infrastructure teams within today's digital businesses need to operate at a speed that leaves little room for manual updates and almost certainly requires automation, suggests Sascha Giese at SolarWinds.